Eating in the City: Diet and Provisioning in Early Nineteenth Century Montreal - Fyson, Donald William (Université McGill, 1989)
Keywords: Alimentation

Residential Mobility in Montreal, 1861-1901 - Gilliland, Jason A. (Université McGill, 1993)
Keywords: Famille; Logement; Mobilité résidentielle

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

Images and Reality of Fatherhood: a Case Study of Montreal's Protestant Middle Class, 1870-1914 - Fish, Cynthia (Université McGill, 1992)
Keywords: Famille; Protestants

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

Rethinking Juvenile Prostitution: Insights from Youths on the Street - Morris, Jason (Université McGill, 1999)
Keywords: Enfants; Prostitution

The Natural Areas of the Montreal Metropolitan Community with Special Reference to the Central Area - Zatuka, Leo (Université McGill, 1948)
Keywords: Parcs

Patterns of Living of Elderly People in Montreal. A Study of the Patterns of Living of 137 People 70 Years of Age and Over Who "Live in Three Different Socio-Economic Areas in Montreal - Adefrissew, Demissie; Cooperberg, Arlene; Driedger, Florence; Driedger, Otto; Ferguson, Janet; Gerima, Yohannes W.; Sims, Valerie; Weinstein, Herbert; Zukerman, Harold (Université McGill, 1958)

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage